Nanoparticle co-delivery of wortmannin and cisplatin synergistically enhances chemoradiotherapy and reverses platinum resistance in ovarian cancer models. (July 2018) - Zhang, Maofan; Hagan, C. Tilden; Min, Yuangzeng; Foley, Hayley; Tian, Xi; Yang, Feifei; Mi, Yu; Au, Kin Man; Medik, Yusra; Roche, Kyle; Wagner, Kyle; Rodgers, Zachary; et al.
Abstract: Most ovarian cancer patients respond well to initial platinum-based chemotherapy. However, within a year, many patients experience disease recurrence with a platinum resistant phenotype that responds poorly to second line chemotherapies. As a result, new strategies to address platinum resistant ovarian cancer (PROC) are needed. Herein, we report that NP co-delivery of cisplatin (CP) and wortmannin (Wtmn), a DNA repair inhibitor, synergistically enhances chemoradiotherapy (CRT) and reverses CP resistance in PROC. We encapsulated this regimen in FDA approved poly(lactic-co-glycolic acid)-poly(ethylene glycol) (PLGA-PEG) NPs to reduce systemic side effects, enhance cellular CP uptake, improve Wtmn stability, and increase therapeutic efficacy. Treatment of platinum-sensitive ovarian cancer (PSOC) and PROC murine models with these dual-drug loaded NPs (DNPs) significantly reduced tumor burden versus treatment with combinations of free drugs or single-drug loaded NPs (SNPs). These results support further investigation of this NP-based, synergistic drug regimen as a means to combat PROC in the clinic.